Comparison of Percutaneous Nephrolithotomy and Anatrophic Nephrolithotomy - Likitwattanasakul, Jamroon (Journal of Health Science of Thailand, 2018)
The purpose of this study was to compare the result, cost and complications of percutaneous nephrolithotomy (PCNL) and anatrophic nephrolithotomy (ANL). A retrospective study of 41 renal stone patients in each group that underwent PCNL and ANL during February - November 2008 at Nakornping hospital were carried out. Data were analysed by t-test. Findings show that the operative time of PCNL group was longer than that of the ANL group (p<0.05). The need for post operative meperidine in PCNL group was less than that of the ANL group (p<0.05). Hospital stay in PCNL group was not significantly less than that of the ANL group (6.59 VS 7.15 days, p 0.24). Residual stones in PCNL group was more than ANL group (p 0.01). Cost of PCNL group was less than that of ANL group (p 0.02). Complications including blood transfusion rate and sepsis were the same and acceptable in both group. Only one patient in PCNL group (2.4%) had mild hydrothorax but needed no intercostal drainage. This study indicates that PCNL is safe and an effective treatment for renal calculi as ANL. PCNL results in short convalescence and lower cost, however the more residual stones rate can be treated with minimally invasive ways as extracorporeal shock wave lithotripsy (ESWL) and ureterorenoscopy (URS).